Monetary policy rules in theory and in practice: Evidence from the UK and the US - Juan Páez-Farrell (Cardiff University, Cardiff Business School, 2007)
Given the large amount of interaction between research on monetary policy and its practice, this paper examines whether some simple monetary policy rules that have been proposed in the academic literature, part of which has originated from within central banks, provide a reasonable characterisation of actual policy in the UK and the US. The paper finds that the simple rule that describes best actual US monetary policy is a speed limit rule with dynamics, whilst for the UK it is a forward-looking rule. The simpler dynamics in the UKís monetary policy rule are reflective of the lower persistence of inflation as a result of its policy of inflation targeting.
Keywords: 330; Geldpolitik; Regelgebundene Politik; Taylor-Regel; Inflation Targeting; Großbritannien; USA